Economic evaluations of pharmacological and non-pharmacological interventions for delirium: A systematic review and meta-analysis - Md Parvez Mosharaf; Khorshed Alam; Jeff Gow; Rashidul Alam Mahumud (SSM - Mental Health)
Background: Delirium, a prevalent cognitive dysfunction in older adults, particularly in hospital and surgical settings, significantly increases patient morbidity, mortality, and healthcare costs. However, economic evaluations of healthcare interventions aimed at its prevention, management, and treatment are scant. This study synthesized the available economic evaluation evidence on both pharmacological and non-pharmacological interventions. Methods: A systematic review was conducted on studies published from January 1, 2000, to December 31, 2023, across multiple databases, including PubMed, MEDLINE, Scopus, and EBSCOhost (CINAHL, PsycINFO, and ECOLIT). We adhered to the PICOS framework for inclusion and exclusion criteria and followed PRISMA guidelines for the analysis. The quality of the studies included was assessed using the CHEERS checklist. The meta-analysis of the cost-effectiveness of multicomponent non-pharmacological intervention was evaluated using incremental net benefits (INB). Results: Sixteen eligible studies met the inclusion criteria including four cost-effectiveness analyses (CEA), two cost-benefit analyses (CBA), three cost-consequence analyses (CCA), and seven cost-saving/minimization analyses. The majority (14/16 studies) evaluated non-pharmacological interventions, while only two studies assessed the cost-effectiveness of drug interventions (i.e. dexmedetomidine). Besides the cost-effective multicomponent interventions, pharmacological intervention was also associated with a cost reduction of a maximum of US$4370 per patient by decreasing the length of ICU stays. The studies predominantly originated from high-income countries. The meta-analysis included four studies and pooled INB of multicomponent non-pharmacological intervention was estimated at US$8014 (95% CI=US$1,060, US$14,969; p-value<0.05) with significant heterogeneity among the studies (I2 = 100%; p-value<0.01). The pooled INB was US$2657 higher for the model-based economic evaluation studies compared to within-trial evaluation. Conclusion: The estimated INB indicated that multicomponent non-pharmacological intervention was a cost-effective strategy to prevent and manage delirium cases which indicates improved patient outcomes and potential cost savings. Future research should focus on low-resource settings and direct comparisons of pharmacological and non-pharmacological approaches to further enhance delirium management practices.